THE PROBLEM OF PARAMETRIC SYNTHESIS OF SYSTEMS TO ENSURE DATA INTEGRITY IN INFORMATION SYSTEMS AND METHOD FOR ITS SOLUTION - Gennady A. Berketov; Andrey A. Mikrukov; Anatoly P. Tsurkin (Открытое образование (Москва))
In the article the mathematical model of the recovery process data in information systems is considered. We propose a method to optimize the regeneration copies of the database used in the recovery of information.